KIPRAH POLITIK PARTAI GERINDRA (Studi Tentang Strategi Pemenangan Calon Legislatif Terpilih Partai Gerindra dalam Pemilu 2014 di Kota Salatiga) - Carry Heart Kandowangko; Pamerdi Giri Wiloso; Elly Esra Kudubun (Universitas Kristen Satya Wacana, 2014)
Elections (elections) in addition to the circulation succession is understood as a five-yearly political as well as a means of popular sovereignty, and